Comparison of the efficacy and safety of a new recombinant human follicle-stimulating hormone (DA-3801) with follitropin-α (Gonal-F®) in women undergoing controlled ovarian hyperstimulation for assisted reproductive technology - Moon, Shin Yong; Choi, Young Sik; Ku, Seung-Yup; Kim, Seok Hyun; Choi, Young Min; Kang, Inn Soo; Kim, Chung Hoon (The journal of obstetrics and gynaecology research, 2007)
Aim:  To compare the efficacy and safety of a new recombinant human follicle‐stimulating hormone (FSH; DA‐3801) with follitropin‐α (Gonal‐F®) in women undergoing controlled ovarian hyperstimulation (COH) for assisted reproductive technology (ART). Methods:  This was a phase III, multicenter, randomized, non‐inferiority study. A total of 97 women were randomized to receive COH using DA‐3801 (DA‐3801 group, n = 49) or Gonal‐F® (Gonal‐F group, n = 48). All subjects underwent COH using a gonadotropin‐releasing hormone (GnRH) antagonist protocol. The primary efficacy endpoint was the number of oocytes retrieved, and the secondary efficacy endpoints included the total dose of FSH, the duration of stimulation, the serum estradiol levels on the day of human chorionic gonadotropin (hCG) administration, and the fertilization, implantation and pregnancy rates. Safety was evaluated using pre‐ and post‐treatment laboratory tests and all adverse events were recorded. Results:  The number of oocytes retrieved was 13.0 ± 6.2 (DA‐3801) versus 10.6 ± 6.7 (Gonal‐F) in the intention‐to‐treat (ITT) population, and 12.7 ± 6.4 (DA‐3801) versus 11.0 ± 7.1 (Gonal‐F) in the per‐protocol (PP) population. The non‐inferiority of DA‐3801 was demonstrated with differences of 2.3 ± 6.5 (95% confidence interval [CI] = 0.13, ∞) and 1.7 ± 6.7 (95% CI = −0.74, ∞), respectively, in the ITT and PP populations. The total dose of FSH used (1789.8 ± 465.5 vs 2055.6 ± 646.7 pg/mL, P = 0.027) and duration of stimulation (8.3 ± 1.4 vs 9.1 ± 1.9 days, P = 0.036) in the ITT population were significantly lower in the DA‐3801 group. Other secondary efficacy endpoints, including pregnancy and implantation rates and the incidence and severity of adverse events, were comparable between the two groups. Conclusions:  The results of this study demonstrate that DA‐3801 is not inferior to follitropin‐α in terms of its efficacy and safety in women undergoing COH for ART.